REVIEW OF EAU GUIDELINES ON THE TREATMENT AND FOLLOW-UP OF NON-NEUROGENIC MALE LOWER URINARY TRACT SYMPTOMS INCLUDING BENIGN PROSTATIC OBSTRUCTION - K. L. Lokshin (Вестник урологии, 2014)
Original Authors: Matthias Oelkea , Alexander Bachmannb , Aure´lienDescazeaudc , Mark Embertond , Stavros Gravas e , Martin C. Michelf , James N’Dowg , Jørgen Nordlingh , Jean J. de la Rosettei aDepartment of Urology, Hannover Medical School, Hannover, Germany; bDepartment of Urology, University Hospital Basel, Basel, Switzerland; cDepartment of Urology, Dupuytren Hospital, University of Limoges, Limoges, France; dDivision of Surgical and Interventional Science, University College London, London, UK; eDepartment of Urology, University of Thessaly, Larissa, Greece; fDepartment of Pharmacology, Johannes-Gutenberg-University, Mainz, Germany; g Academic Urology Unit, University of Aberdeen, Aberdeen, UK; hDepartment of Urology, Herlev Hospital, University of Copenhagen, Herlev, Denmark; iDepartment of Urology, Academic Medical Centre, University of Amsterdam, Amsterdam, The Netherlands EUROPEAN UROLOGY 64 (2013) 118–140, http://dx.doi.org/10.1016/j.eururo.2013.03.004.